Understanding through experience: information, experience and understanding in clinical rehabilitation practice. (June 2014) - Ringstad, Øystein
Abstract Purpose: According to ethical theories of patient autonomy, patients need information and understanding to make their own, autonomous choices. The aim of this article is to describe strategies used by clinical rehabilitation teams to develop patients' understanding and promote their autonomy. Method: Individual semi-structured interviews were conducted with the patient, the nurse, the physiotherapist and the physician of three institution based rehabilitation teams. Analytic procedures described by Strauss and Corbin were applied, identifying categories by their properties and dimensions. Results: The analysis revealed how practitioners recognized that patients needed experience with practical challenges in order to understand their clinical conditions properly. Practitioners disclosed information related to the individual patient's experience with his or her clinical condition. In order to make information relevant to the individual patient's experience of possibilities and limitations, information was disclosed in discussions of these experiences, rather than in abstract verbal explanations. Patients needed to understand their situation to make autonomous choices for their future lives. Conclusions: In clinical rehabilitation, patients and practitioners agree that adequate understanding cannot be achieved by verbal information alone, and that patients need to experience essential aspects of their physical possibilities and limitations. Implications for Rehabilitation Patients need an adequate understanding of their injuries or diseases to be able to make autonomous choices. In clinical rehabilitation teams, practical and bodily experiences are recognized as crucial for patients to develop such understanding. Rehabilitation practitioners may effectively enhance a patient's understanding and autonomy by disclosing information as part of discussions of the patient's own experiences.